Improve Wear Resistance on Al 332 Alloy Matrix- Micro -Nano Al2O3 Particles Reinforced Composite - Mhmood, Ibtihal A.; Mohamed, Adnan dawood; Mohamed, Rawnaq Ahmed (Al-Khwarizmi Engineering Journal, 2017)
The wear behavior of alumina particulate reinforced A332 aluminium alloy composites produced by a stir casting process technique were investigated. A pin-on-disc type apparatus was employed for determining the sliding wear rate in composite samples at different grain size (1 µm, 12µm, 50 nm) and different weight percentage (0.05-0.1-0.5-1) wt% of alumina respectively. Mechanical properties characterization which strongly depends on microstructure properties of reinforcement revealed that the presence of ( nano , micro) alumina particulates lead to simultaneous increase in hardness, ultimate tensile stress (UTS), wear resistances. The results revealed that UTS, Hardness, Wear resistances increases with the increase in the percentage of reinforcement of Al2O3 when compared to the base alloy A332. The wear rates of the composites were considerably less than that of the aluminum alloy at all applied loads with increasing percentage of reinforcement when compared to the base alloy A332.